LEARNING WITH AN INTEGRATED STEM PROJECT BASED LEARNING MODEL TO IMPROVE STUDENTS' CREATIVE THINKING ABILITIES - Ilhami, Aldeva; Mahendra, Tasya (PROGRES PENDIDIKAN, 2024)
Learning using the STEM integrated project based learning model in the 21st century is widely applied in schools, so researchers want to create a literature review for this title. This research uses a systematic literature review method, namely collecting several articles that match the title being studied. Based on the literature selection process (prism method) that has been carried out, it is known that the literature search results (identification) total 3 pieces of literature, 489 pieces of literature sourced from Google Scholar and 352 pieces of literature sourced from Crossruff. The results of this research show that the average N-gain value in the experimental and control classes has a significant difference so that the data obtained is high enough to improve students' creative thinking abilities.